The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1988
DOI: 10.1159/000185055
|View full text |Cite
|
Sign up to set email alerts
|

Protection of Renal Function and of Nutritional Status in Uremic Rats by Means of a Low-Protein, Low-Phosphorus Supplemented Diet

Abstract: A low-protein, low-phosphorus diet supplemented with essential amino acids and keto analogues was given to 12 rats, starting from the 90th day after subtotal nephrectomy. The purpose was to assess its effect on the residual renal function and on the nutritional status in rats with already established severe renal failure. Ten control rats in the same conditions, following a standard diet supplying normal amounts of protein and phosphorus were also studied. The supplemented diet exerted a well-evident protectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…Twelve to 24 weeks of ketoacid treatment enhanced renal function, exemplified by decreased proteinuria, glomerular sclerosis, and tubulointerstitial fibrosis ( Gao et al, 2010 ; Meisinger et al, 1987 ; Zhang et al, 2016 ; Liu et al, 2018 ). Previous studies have reported similar findings ( Maniar et al, 1992 ), in addition to enhanced globular filtration rate and survival in rats ( Barsotti et al, 1988 ). More recently, a study by Wang et al found that 24 weeks of ketoacid treatment in rats with CRF increased body weight, mitochondrial electron transport chain activity and decrease oxidative damage in muscle ( Wang D. et al, 2018 ).…”
Section: Effect Of Different Diseases On Bcaa Catabolism In Skeletal Musclesupporting
confidence: 77%
“…Twelve to 24 weeks of ketoacid treatment enhanced renal function, exemplified by decreased proteinuria, glomerular sclerosis, and tubulointerstitial fibrosis ( Gao et al, 2010 ; Meisinger et al, 1987 ; Zhang et al, 2016 ; Liu et al, 2018 ). Previous studies have reported similar findings ( Maniar et al, 1992 ), in addition to enhanced globular filtration rate and survival in rats ( Barsotti et al, 1988 ). More recently, a study by Wang et al found that 24 weeks of ketoacid treatment in rats with CRF increased body weight, mitochondrial electron transport chain activity and decrease oxidative damage in muscle ( Wang D. et al, 2018 ).…”
Section: Effect Of Different Diseases On Bcaa Catabolism In Skeletal Musclesupporting
confidence: 77%
“…The beneficial role of KAs supplementation on renal function is well established in experimental models, but the effects are different in human clinical trials. LPD/VLPD + KAs were able to decrease proteinuria, renal fibrosis, and severe glomerular sclerosis in different CKD rodent models, as disclosed in Table 2 [9,10,13,14,15,17,18,19]. However, the majority of these preclinical studies have compared a normal protein diet vs. VLPD/LPD + KAs.…”
Section: Do Ketoacid Analogues Have An Impact On Renal Function Anmentioning
confidence: 99%
“…However, the majority of these preclinical studies have compared a normal protein diet vs. VLPD/LPD + KAs. It is, therefore, difficult to decipher the specific effect of the KAs supplementation [9,10,15,17,18,19]. Gao et al highlighted that supplementation of KAs increased the Kruppel-like factor-15, which is a transcription factor shown to reduce fibrosis in 5/6 nephrectomized rats [14].…”
Section: Do Ketoacid Analogues Have An Impact On Renal Function Anmentioning
confidence: 99%
“…Studies in CKD rodent models have suggested a strong positive correlation between dietary phosphate consumption and CKD progression (2,3,14,18,19,24,25,48). Moreover, serum concentrations of FGF23 in patients predict a higher risk for loss of kidney function in both native and transplanted kidneys (11,30,43).…”
Section: Introductionmentioning
confidence: 99%